2016
DOI: 10.1186/s13613-016-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of external PEEP in patients under controlled mechanical ventilation with an auto-PEEP of 5 cmH2O or higher

Abstract: BackgroundIn some patients with auto-positive end-expiratory pressure (auto-PEEP), application of PEEP lower than auto-PEEP maintains a constant total PEEP, therefore reducing the inspiratory threshold load without detrimental cardiovascular or respiratory effects. We refer to these patients as “complete PEEP-absorbers.” Conversely, adverse effects of PEEP application could occur in patients with auto-PEEP when the total PEEP rises as a consequence. From a pathophysiological perspective, all subjects with flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…In a mixed population of COPD patients and patients with acute respiratory failure, when there was expiratory flow limitation, the higher external PEEP significantly reduced the intrinsic PEEP, which was “absorbed” in the total PEEP. In contrast, in patients without expiratory flow limitation, the intrinsic PEEP did not change and the total PEEP could be increased [12, 48].…”
Section: Discussionmentioning
confidence: 99%
“…In a mixed population of COPD patients and patients with acute respiratory failure, when there was expiratory flow limitation, the higher external PEEP significantly reduced the intrinsic PEEP, which was “absorbed” in the total PEEP. In contrast, in patients without expiratory flow limitation, the intrinsic PEEP did not change and the total PEEP could be increased [12, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Application of extrinsic PEEP might eliminate the EFL by counteracting the pleural pressure at the choke point, which improves air-trapping and reduces patient's work of breathing 29,30 . This concept is supported by Natalini et al 29 study, which demonstrated that the extrinsic PEEP could abolish the auto PEEP.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, 60% of the patients with unsuccessful extubation had EFL 9,28 . Previous studies showed that positive end expiratory pressure (PEEP) 29,30 , upright position 31 , bronchodilator 32 , and diuretics 33 possibly improved extubation outcomes in the patients with EFL.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of EFL has been previously demonstrated in other patients so that it could be hypothesised that an unknown amount of ICU patients other than COPD can exhibit EFL. This could have relevant clinical consequences since the presence of EFL has numerous side effects [1], such as the presence of PEEPi [32] that might have detrimental effects on respiratory efficiency and cardiovascular function. Further, the reduction of the expiratory flow and the inability to increase it by the expiratory muscle contraction decrease the efficacy of cough and secretion removal [14] favouring the development of atelectasis, bronchitis and pneumonia.…”
Section: Discussionmentioning
confidence: 99%